The wolf in the landscape: Antonio Cesena and attitudes to wolves in sixteenth century Liguria - Hearn, Robert; Balzaretti, Ross; Watkins, Charles (Cambridge University Press, 2015)
The recent reappearance of wolves in many areas of Europe has stimulated an interest in the past relationships between the species and humans in various different geographical locations and historical epochs. The image of wolves approaching and entering human settlements is a potent image of the wild, ‘natural’ world encroaching on that of the domestic and ‘cultural’. This paper examines the existence of the wolf in the psychological and physical landscape. It does so through a micro-historical analysis of a vernacular manuscript from the mid sixteenth century in north-west Italy. The paper demonstrates that the wolf existed both as a ‘mythological beast’ and as a ‘biological animal’ that was a normal, frequently encountered component of the Ligurian faunal assemblage.